Variability of herbage production in mixed leys as related to ley age and environmental factors: a farm survey - Riesinger, Paul; Herzon, Irina (MTT Agrifood Research Finland, 2008)
Influences of ley age, soil properties, and geographical location on the herbage production of red clover-grass leys were determined under practical conditions on 27 organic farms located in the southern and in the northwestern coastal regions of Finland. Averaged over one-, two-, and three-year-old leys the accumulated first and second cuts produced 7.12 t dry matter herbage ha-1 year-1, with a clover proportion of 34.8%. Herbage production declined with increasing ley age. The average proportion of clover increased from 26.4% in the first to 43.7% in the second cut but decreased with ley age. Within- and between-field variations of clover proportions markedly decreased from the first to the second cut and strongly increased with ley age, while changes in the variations of herbage production were less pronounced. Within-field variations of clover proportions in the first and in the second cuts were higher at lower proportions of clover. Herbage production was positively related with clover proportion. Soil properties had a major impact on clover proportion and herbage production, largely explaining also regional differences in ley growth. Amelioration of fields and, not at least, of less fertile sites within the same field seems to be a crucial requirement for higher and more even clover proportions and herbage yields.
Keywords: Ka; Finland; organic farming; proportion of clover; red clover-grass ley; soil properties; spatial heterogeneity; Trifolium pratense